The Effect of Occupational Safety and Health Programs, Workload on Employee Performance Mediated by Work Stress - M. Yasin Ibrahim; Veni Devialesti (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2023)
The Occupational Safety and Health (OSH) program which is one of the human rights and one of the efforts in improving employee performance in the company itself. This research aims to determine the effect of the Occupational Safety and Health program and workload on employee performance which is mediated by work stress at PT. Sinarjaya Inti Mulya Srengsem work unit. The research method used is comparative quantitative research, where variables are measured using a Likert scale. The number of samples in this research was 70 employees of PT. Sinarjaya Inti Mulya Srengsem work unit. The data collection techniques in this research used document studies, questionnaires, and interviews. Data analysis techniques using Structural Equational Modeling (SEM) using Smart-PLS. The research results showed that the OSH Program has a positive and significant effect on employee performance, workload, and work stress has a negative and significant effect on employee performance, the OSH Program has a negative but not significant effect, workload has a positive and significant effect on work stress, the OSH Program mediated work stress does not have a significant effect on employee performance, work conditions mediated by work stress have a significant effect on employee performance.